Comparison of Leasing and Ijarah Accounting : A Critical Research of Indonesian Financial Accounting Standards - Saputra, Wali (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The Financial Accounting Standards Statement (FASS) 107, which governs the domain of leasing accounting, has elicited unfavorable interpretations among accounting practitioners in Indonesia. Practitioners assert that FASS 107 bears no significant distinction from FASS 30, which also addresses the issue of leasing accounting, as the principles of ijarah accounting delineated in FASS 107 are perceived to have incorporated numerous principles from leasing accounting in FASS 30 by substituting conventional terminology with sharia-compliant terminology. The objective of this study is to conduct a comparative analysis of the similarities and distinctions between the principles of leasing accounting articulated in FASS 30 and the principles of ijarah accounting outlined in FASS 107. This research is classified as library research. The primary data source utilized comprises the Financial Accounting Standards containing the regulations associated with FASS 30 and FASS 107, which have been published by the Indonesian Institute of Accountants, while the secondary data source comprises the National Sharia Council (DSN) Decree Number 27/DSNMUI/III/2002, dated March 28, 2002 which pertains to leasing financing, among other relevant documents. The analytical model employed in this study is the content analysis technique applicable to FASS 30 and FASS 107. Subsequently, the researcher employs a comparative analysis approach to both FASSs, supplemented by arguments aimed at substantiating the similarities and differences in the accounting principles encapsulated within the two FASSs. The findings of the study reveal that FASS 107, pertaining to leasing accounting, continues to adopt numerous principles of leasing accounting delineated in FASS 30. There are five notable similarities in the accounting principles embraced by FASS 107. Furthermore, the findings also substantiate that there exist fourteen distinctions in the accounting principles employed by the two FASSs. The study concludes by affirming that discrepancies exist between the leasing accounting principles in FASS 30 and the ijarah accounting principles in FASS 107.